Proleptic priests. - Scholer, John M. (Library of New Testament studies., 1991)
In no other New Testament writing does the interest in the cult and its practice figure more prominently than in the Epistle to the Hebrews. Whereas scholarly research has preoccupied itself with the high priesthood of Christ, comparatively little consideration has previously been given to the implied priesthood of the readers. Scholer begins with an examination of the role and function of the priesthood found in the Old Testament, Pseudepigrapha, Qumran, rabbinic, Philo and mystery traditions. His second goal is to discover why the readers of Hebrews may be described as priests, and how the h.